Addressing Foreign Worker Regulations in Indonesia Post-Job Creation Law: Challenges and Solutions - Ayu Putri Rainah Petung Banjaransari (Constitutionale)
Issues in Indonesia's labor law stem from the influx of foreign workers and their impact on domestic employment. This recurring problem arises as foreign investment brings in experts or laborers from their home countries, often leading to conflicts with local workers. Indonesia's sizable population does not correspond with available job opportunities, resulting in unemployment and economic disparities across regions. Consequently, the renewal of Indonesia's Job Creation Law of 2020 and its accompanying regulations are crucial. This research adopts a normative legal research method, focusing on secondary legal materials to analyze the legal framework and conceptual aspects related to foreign labor regulations post the Job Creation Law. It identifies challenges within the new regulations and proposes solutions to address them effectively.